ANALISIS KOMUNIKASI PEMASARAN LISTRIK PRABAYAR PT. PLN (Persero) RAYON NEGARA DAN PENGARUHNYA TERHADAP PEMBENTUKAN CITRA PERUSAHAAN - Putri Anggreni; Ni Luh Gede Pradnya Swandewi (STIMI Handayani Denpasar, 2020)
The purpose of this research is to explain and describe about electrical communication prepaid PT. PLN (Persero) Rayon Negara and to know the influence of marketing communication prepaid electricity PT. PLN (Persero) Rayon Negara against the formation of corporate image. By marketing communication as independent variable and Corporate Image as dependent variable. This research uses the research instrument in the form of questionnaires with a sample of 98 respondents. Data collection using field research method, literature study, documentation, data source and data type. Data analysis technique used descriptive statistic analysis, normality test, homogeneity test, heteroscedasticity test, auto correlation test, t test (Hypothesis) and F-test (Hypothesis) previously tested the validity and reliability to test the questionnaire with SPSS Version 20 for Windows. The results stated that in communicating the marketing of electricity prepaid PT. PLN (Persero) Rayon Negara with incentive to socialize to the community through 2 (two) ways: 1) Personal marketing; 2) Non-personal marketing and then the influence of marketing communication prepaid electricity PT. PLN (Persero) Rayon Negara on the formation of corporate image that, sig (2-tailed) and marketing communications and image of company is smaller than 0,05 so H 0 is rejected and H accepted. This states that the influence between independent variables Marketing Communication (X) and dependent variable Company Image (Y) studied.